Isolated ovarian metastasis of gastric cancer: Krukenberg tumor - Uyeturk, Ummugul; Arslan, Serife Hulya; Bal, Oznur; Arslan, Ulku Yalcintas; Oksuzoglu, Omur Berna Cakmak (Contemporary Oncology/Współczesna Onkologia, 2013)
Introduction: Gastric cancer, one of the most common cancers in the world, rarely metastasizes to the ovaries. Ovarian metastases of gastric signet ring cell cancer (SRCC) are referred to as Krukenberg tumors and account for 1–2% of all ovarian cancers. Here, we analyze the characteristics, treatment, and prognosis of patients with Krukenberg tumors. Material and methods: We retrospectively analyzed the demographic characteristics, treatment modalities, progression-free survival (PFS), and overall survival (OS) of patients who were diagnosed with Krukenberg tumors of gastric cancer origin and who underwent treatment and follow-up between January 2005 and January 2012 in the Ankara Oncology Education and Research Hospital. Results : Among 1755 patients diagnosed with gastric cancer between January 2005 and January 2012, eight patients (0.45%) with histopathologically identified Krukenberg tumors were enrolled. The median age of the eight patients was 42.2 years (range, 32–69 years). Two (25%) of the patients were stage 3A, two (25%) were stage 3C, and four (50%) were stage 4 at the time of diagnosis. The median PFS was 13.2 months (1–25 months), the median OS after the original diagnosis was 16.7 months (1–41 months), and the median OS after ovarian metastasis was 3.6 months (1–10 months). Discussion: Krukenberg tumors were seen particularly in young patients and more frequently during the premenopausal period. The prognosis was poor. When only the ovaries were affected, metastasectomy prolonged the survival time.